Reduced Innate Immune Response to a Staphylococcus aureus Small Colony Variant Compared to Its Wild-Type Parent Strain - Ou, Judy J. J.; Drilling, Amanda J.; Cooksley, Clare; Bassiouni, Ahmed; Kidd, Stephen P.; Psaltis, Alkis J.; Wormald, Peter J.; Vreugde, Sarah (Frontiers in Cellular and Infection Microbiology, 2016)
Background:Staphylococcus aureus (S. aureus) small colony variants (SCVs) can survive within the host intracellular milieu and are associated with chronic relapsing infections. However, it is unknown whether host invasion rates and immune responses differ between SCVs and their wild-type counterparts. This study used a stable S. aureus SCV (WCH-SK2SCV) developed from a clinical isolate (WCH-SK2WT) in inflammation-relevant conditions. Intracellular infection rates as well as host immune responses to WCH-SK2WT and WCH-SK2SCV infections were investigated. Method: NuLi-1 cells were infected with either WCH-SK2WT or WCH-SK2SCV, and the intracellular infection rate was determined over time. mRNA expression of cells infected with each strain intra- and extra-cellularly was analyzed using a microfluidic qPCR array to generate an expression profile of thirty-nine genes involved in the host immune response. Results: No difference was found in the intracellular infection rate between WCH-SK2WT and WCH-SK2SCV. Whereas, extracellular infection induced a robust pro-inflammatory response, intracellular infection elicited a modest response. Intracellular WCH-SK2WT infection induced mRNA expression of TLR2, pro-inflammatory cytokines (IL1B, IL6, and IL12) and tissue remodeling factors (MMP9). In contrast, intracellular WCH-SK2SCV infection induced up regulation of only TLR2. Conclusions: Whereas, host intracellular infection rates of WCH-SK2SCV and WCH-SK2WT were similar, WCH-SK2SCV intracellular infection induced a less widespread up regulation of pro-inflammatory and tissue remodeling factors in comparison to intracellular WCH-SK2WT infection. These findings support the current view that SCVs are able to evade host immune detection to allow their own survival.